Prevalência da mutação ser-249 no gene TP53 em pacientes com carcinoma hepatocelular e cirrose hepática sem carcinoma hepatocelular diagnosticados em Vitória, Espírito Santo - Carvalho, Fernanda Magri de (2009)
The hepatocellular carcinoma (HCC) incidence has large geographic variation, which is associated with the different prevalences of its most common etiological factors. Although its real incidence in the Espirito Santo State is not known, the HCC is frequently diagnosed in ES associated with hepatitis B (HBV) and C virus infections. However, approximately 40% of the cases do not present known etiological factors. Therefore, it was the purpose of this study to verify if another factor - aflatoxins - could be involved in the HCC etiology in ES. In tropical areas, the aflatoxins are considered an important etiological factor of CHC, especially when associated with HBV infection. The aim of this investigation was to study the prevalence of the specific ser-249 mutation in the TP53 gene was studied, that indicates indirect food contamination with aflatoxins and its association with HBV infection. Forty-one HCC samples and seventy-four hepatic cirrhosis samples were investigated, using PCRRFLP methodology and sequencing. The HBV DNA was amplified with specific primers targeting six different regions of its genome. Primers were chosen considering the most conserved regions of the viral genome and encompassing the eight known genotypes of HBV. Presence of HBV DNA was observed in 46% (19/41) of the hepatocellular carcinoma cases studied. The ser-249 TP53 mutation was observed in 15% (6/41) and 1,5% (1/69) of the HCC and cirrhosis cases respectively, not having statistical correlation with the presence of HBV DNA. Other four mutations in TP53 codon 250 were found, yielding a total mutation prevalence of 24% (10/41), considering both ser-249 and codon 250 mutations, possibly also associated with food contamination by aflatoxins, and suggesting an alimentary exposition to aflatoxins in Espirito Sant